2012
DOI: 10.1177/146499341101200309
|View full text |Cite
|
Sign up to set email alerts
|

Is ICT the panacea to sub-Saharan Africa’s development problems? Rethinking Africa’s contentious engagement with the global information society

Abstract: The explosion in mobile phone subscription notwithstanding, benefits from ICT deployment are far from being realized in sub-Saharan Africa (SSA). A clash between the rationality for development and local systems of reasoning, and the failure to cultivate behaviours that support technological innovation provide little hope for sustained information and communication technology (ICT) adoption in the region. The article discusses failures in technological innovation and then explores ways that SSA countries can m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…This agrees with many other studies that empirically confirmed the significant influence of the socio-economic characteristics of farmers in their adoption of ICTs for marketing and production decisions in specific farming systems (Nwafor, 2019;Waqas et al, 2015;Oluwatayo, 2014;Kyem, 2012;Bagchi & Udo, 2007).…”
Section: Existing Farmers' Information and Communication Technology Asupporting
confidence: 91%
See 1 more Smart Citation
“…This agrees with many other studies that empirically confirmed the significant influence of the socio-economic characteristics of farmers in their adoption of ICTs for marketing and production decisions in specific farming systems (Nwafor, 2019;Waqas et al, 2015;Oluwatayo, 2014;Kyem, 2012;Bagchi & Udo, 2007).…”
Section: Existing Farmers' Information and Communication Technology Asupporting
confidence: 91%
“…Research shows that individual characteristics are important indicators for technology adoption (Ali and Kumar, 2011;Oluwatayo, 2014), and to effectively incorporate ICTs, both the cultural context and specific characteristics of both adaptors and innovations must be taken into consideration (Kyem 2012). Individual attributes also influence the need for information, as well as the capacity to obtain and utilize such information (Israel and Wilson, 2006).…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…Since electricity, radio, TV and telephones among others are agents of massive transformation they might hold the key to ideational change in thinking and behavior towards massive increase in contraceptive use if well appropriated as vehicle of change by family planning policies stakeholders and program implementers. [29][30][31][32]…”
Section: Discussionmentioning
confidence: 99%
“…8 The literature showed that key agents of modernity that may influence behaviour change include electricity television, mobile phone. [29][30][31][32] These agents of modernity were included in models designed to examine factors influencing contraceptive use in the region. The literature confirms strong positive relationship between contraceptive use and number of living children.…”
Section: Introductionmentioning
confidence: 99%
“…EICT is considered crucial for most SMEs as small businesses are supposedly spending many resources to minimize costs and improve an organization’s performance (Tob-Ogu et al, 2018; Yen Teoh & Pan, 2008). However, a large number of small businesses are still confronted with such adoption barriers as poor education, poor adoption plans, poor management, and inadequate awareness of the benefits of ICT (Asongu & Le Roux, 2017; Kyem, 2012). Scholars submit that valuable contributions to ICT matters are the aftermath of poor preparation to adopt, which often gives rise to short-term decisions as the majority of SMEs allow ICT adoption decisions to be taken by few players within the organization (Kayisire & Wei, 2016; Rantapuska & Ihanainen, 2008), while others appear to be busy with the SMEs’ day-to-day business activities (Ocda, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%